2003
DOI: 10.1016/s0895-7061(03)00858-6
|View full text |Cite
|
Sign up to set email alerts
|

Urinary tetrahydroaldosterone as a screening method for primary aldosteronism: a comparative study

Abstract: The data suggest that tetrahydroaldosterone is the most reliable screening test for PA. Tetrahydroaldosterone determination in combination with aldosterone-18-glucuronide and free aldosterone increases diagnostic specificity for PA. Potassium, renin, plasma aldosterone, and basal PARR are inadequate screening procedures because they are subject to high rates of false-positive and false-negative results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
1
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 24 publications
2
39
1
4
Order By: Relevance
“…Also, Ulick et al did not find a significant difference between essential hypertension and primary aldosteronism when measuring urinary tetrahydroaldosterone (35). Contrary to these findings, Abdelhamid et al reported a sensitivity and specificity of 95% and 96% for tetrahydroaldosterone and 91% and 71%, respectively, for aldosterone-18-glucuronide (22) in a large study population of 1865 patients using the same assay as in our study. Evaluation of the data differs in that Abdelhamid's group calculated the metabolite concentration as mg/day whereas we expressed the excretion per gram of creatinine in order to correct collection errors.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…Also, Ulick et al did not find a significant difference between essential hypertension and primary aldosteronism when measuring urinary tetrahydroaldosterone (35). Contrary to these findings, Abdelhamid et al reported a sensitivity and specificity of 95% and 96% for tetrahydroaldosterone and 91% and 71%, respectively, for aldosterone-18-glucuronide (22) in a large study population of 1865 patients using the same assay as in our study. Evaluation of the data differs in that Abdelhamid's group calculated the metabolite concentration as mg/day whereas we expressed the excretion per gram of creatinine in order to correct collection errors.…”
Section: Discussioncontrasting
confidence: 86%
“…This is thought to have the advantage of being independent of circadian variations in plasma levels (22,23). Aldosterone is excreted mainly as tetrahydroaldosterone after metabolization in the liver, and as aldosterone-18-glucuronide produced mainly in the kidney (24).…”
Section: Introductionmentioning
confidence: 99%
“…This is in contrast to the reports by other groups. 18 In addition, sensitivity and specificity could not be improved by the correction for sodium excretion. However, the correction of urinary aldosterone metabolites, especially free aldosterone, for plasma renin concentration rendered acceptable profiles and a very high specificity.…”
Section: Discussionmentioning
confidence: 99%
“…17 Aldosterone is excreted in the urine in three main forms: aldosterone-18-glucuronide (A18G), urinary unconjugated (free) aldosterone (A UR ) and tetrahydroaldosterone (THA), which reflects up to 45% of aldosterone secretion. 18 Urine analysis (24 h) for aldosterone metabolites eliminates most of the posture fluctuations in aldosterone blood values, diurnal variations and episodic secretion of aldosterone by the adrenal glands. The urinary unconjugated (free) aldosterone-to-active renin ratio (A UR /R) proved to be a good independent predictor for surgical curability after adrenalectomy, in subjects with aldosteroneproducing adenomas (APAs).…”
Section: Introductionmentioning
confidence: 99%
“…For example, PA has been confirmed in patients with plasma aldosterone levels as low as 9 ng/dL. 27 Falsely high serum potassium levels can occur if patients are asked to repeatedly clinch their fists to facilitate blood collection, which, in turn, may obscure evidence of PA. 28,29 To avoid such an effect, blood should ideally be collected without use of this maneuver.…”
Section: Screening For Pamentioning
confidence: 99%